2017
DOI: 10.24874/ti.2017.39.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tribological performance of Coconut Shell Ash Particle Reinforced Al-Si-Fe Composites using Grey-Fuzzy Approach

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…After removal of slag from the surface, preheated (up to 300 0 C) CSA particles were added into the vortex of the melt during stirring. [5] The mixture is allowed to stir at 600 rpm for 10 min. The melt is allowed into a two finger die of 270mm length and 22mm diameter while stirring.…”
Section: Methodsmentioning
confidence: 99%
“…After removal of slag from the surface, preheated (up to 300 0 C) CSA particles were added into the vortex of the melt during stirring. [5] The mixture is allowed to stir at 600 rpm for 10 min. The melt is allowed into a two finger die of 270mm length and 22mm diameter while stirring.…”
Section: Methodsmentioning
confidence: 99%
“…In situ mixing of compounds is able to improve thermo-mechanical properties by thermal treatment. 35,38,40…”
Section: Resultsmentioning
confidence: 99%
“…XRD spectrum (Figure 1) of reinforced material shows various compounds which exist in CSA, which is basically alumino-silicate. 35,38,40 Mechanical properties of Al-CSA MMC From Table 5, it can be observed that composite hardness values are increasing with volume of CSA, owing to tough phase ceramic compounds and alkaline compounds presented in CSA particles as well as dispersed in cast composite. The tensile strength increases with increasing of volume of CSA, attributes to enhanced grain growth and intermolecular attraction among particulates.…”
Section: Characterization Of Csapmentioning
confidence: 99%
“…The composites are fabricated using double stir casting. The casting process explained elsewhere [20,21]. The counter pin has a dimension of 6 mm in diameter and 27 mm in length.…”
Section: Fabrication and Testing Of Al-lsp Compositesmentioning
confidence: 99%